Pedagogia do Esporte: tensão na ciência e o ensino dos Jogos Esportivos Coletivos - Larissa Rafaela Galatti; Riller Silva Reverdito; Alcides José Scaglia; Roberto Rodrigues Paes; Antonio Montero Seoane (Revista da Educação Física)
Resumo: